2019
DOI: 10.1088/1742-6596/1402/2/022079
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of genetic algorithms and Particle Swarm Optimization (PSO) algorithms in course scheduling

Abstract: Making lecture schedules is a complicated matter because it involves many parties and resources. In order to arrange the schedule optimally, a method is needed that can produce the best optimization value. In this paper, we will discuss the comparison of Genetic Algorithms and Particle Swarm Optimization to design lecture schedules. Once implemented, then comparative analysis of the results of the course scheduling process is carried out by comparing the fitness value and execution speed of the two algorithms.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 3 publications
0
5
0
1
Order By: Relevance
“…In this report, is more successful in evolving larger networks and the PSO is more successful on smaller networks. Ramdania et al [36] has reported that the PSO fitness value outperforms the genetic algorithm, but the genetic algorithm execution time is faster than the PSO algorithm. PSO involves less overall computation effort than GA but shown to outperform the GA for smaller population sizes [37].…”
Section: Resultsmentioning
confidence: 99%
“…In this report, is more successful in evolving larger networks and the PSO is more successful on smaller networks. Ramdania et al [36] has reported that the PSO fitness value outperforms the genetic algorithm, but the genetic algorithm execution time is faster than the PSO algorithm. PSO involves less overall computation effort than GA but shown to outperform the GA for smaller population sizes [37].…”
Section: Resultsmentioning
confidence: 99%
“…Pada penelitian lainnya dilakukan perbandingan GA dan PSO. Hal ini sesuai pada makalah [25], nilai kesesuaian PSO mengungguli GA sehingga PSO memiliki kecenderungan nilai fitness lebih baik dari GA. Tetapi kecepatan eksekusi GA memiliki waktu yang lebih cepat dibandingkan PSO.…”
Section: Analisis Algoritmaunclassified
“…) and lower limit ( ) of the design variable (Ramdania et al [23]), as shown in equations (1) and (2).…”
Section: Optimizationmentioning
confidence: 99%
“…By this initialization process, a swarm of particles can be distributed randomly to the design space. The position and velocity vectors are shown below [23]:…”
Section: Optimizationmentioning
confidence: 99%
See 1 more Smart Citation